2019
DOI: 10.1007/s11912-019-0787-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity on Breast Cancer Diagnosis and Treatment

Abstract: Purpose of Review Obesity is a recognized risk factor for the development of breast cancer and recurrence even when patients are treated appropriately. We reviewed the literature that addresses the impact of obesity on diagnosis and the individual therapeutic interventions, and present a summary of the findings. Recent Findings Compared to non-obese women with breast cancer, obese women with breast cancer have a worse disease-free and overall survival despite appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
202
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(219 citation statements)
references
References 58 publications
(58 reference statements)
4
202
1
12
Order By: Relevance
“…However, the pathway and the inhibitor BEZ235 has not been analyzed in the context of heterotypic interactions between breast cancer cells and adipocytes, which are main cellular components especially in obese conditions. A recent review noticed that the efficacy of cancer treatments is significantly lower in obese breast cancer patients [32]. Our results in the present study suggest that the PI3K-AKT-mTOR pathway is crucial in the adipocyte-mediated breast cancer progression and that dual inhibitors targeting PI3K and mTOR such as BEZ235 could be a good option to inhibit the obesity-breast cancer link.…”
Section: Discussionsupporting
confidence: 60%
“…However, the pathway and the inhibitor BEZ235 has not been analyzed in the context of heterotypic interactions between breast cancer cells and adipocytes, which are main cellular components especially in obese conditions. A recent review noticed that the efficacy of cancer treatments is significantly lower in obese breast cancer patients [32]. Our results in the present study suggest that the PI3K-AKT-mTOR pathway is crucial in the adipocyte-mediated breast cancer progression and that dual inhibitors targeting PI3K and mTOR such as BEZ235 could be a good option to inhibit the obesity-breast cancer link.…”
Section: Discussionsupporting
confidence: 60%
“…Unfortunately, de novo or acquired resistance could be developed, leading to disease progression and increased mortality, which could be amplified in overweight women [9]. Some authors demonstrated that aromatase inhibitors may be less efficient than tamoxifen in overweight and obese patients [10]. Tx resistance seems to be multifactorial with, for example, the lack of ER function or disruption of signaling pathways (RTK, PI3K, NF-kB) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the consumption of these products while limiting vegetable oils, full-fat milk products, and red meat should be the foundation of the diet of every woman who cares about her health (50). It is also worth noting that a diet taking into account an adequate supply of omega-3 fatty acids is also an element of prevention of obesity, which is not only a disease in itself, but is also an important risk factor for cancer -including breast cancer (51). Similar to many previous studies, the results of our analysis indicate a protective (in relation to breast cancer) effect of normal body weight.…”
mentioning
confidence: 99%